2013
DOI: 10.1590/s1677-5538.ibju.2013.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Single scrotal incision orchiopexy - a systematic review

Abstract: Single scrotal incision orchiopexy proved to be an effective technique and is associated with low rates of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
2
22
0
4
Order By: Relevance
“…At a mean follow-up of 48.3 months, the success rate in this series was 98%. This result is comparable with that found in the published literature [13,14]. Any case of postoperative acquired inguinal hernia or hydrocele was not encountered, and conversion to inguinal orchiopexy was not required during any trans-scrotal cases.…”
Section: Discussionsupporting
confidence: 89%
“…At a mean follow-up of 48.3 months, the success rate in this series was 98%. This result is comparable with that found in the published literature [13,14]. Any case of postoperative acquired inguinal hernia or hydrocele was not encountered, and conversion to inguinal orchiopexy was not required during any trans-scrotal cases.…”
Section: Discussionsupporting
confidence: 89%
“…Surgery for palpable testes includes orchidolysis and orchidopexy, either via an inguinal or scrotal approach. The latter approach is mainly reserved for low-positioned, undescended testes, with the pros and cons of each method being weighed against each other [40].…”
Section: Surgical Therapymentioning
confidence: 99%
“…A systematic review showed that overall success rates ranged from 88% to 100%, with rates of recurrence and postoperative testicular atrophy or hypotrophy of <1% [40].…”
Section: Surgical Therapymentioning
confidence: 99%
“…Overall, success rates ranged from 88-100%. 42 In comparison to standard inguinal orchidopexy, recent evidence from observational studies has suggested that the scrotal approach has equivalent success rates and complications, with advantage of a significantly shorter operative time. 38,39,43 At least two randomized, controlled trials comparing the two techniques (inguinal vs. scrotal) have been attempted and essentially confirmed those findings; 44,45 however, in one of the studies the authors also report mean length of stay above two days for both procedures, which questions the generalizability of the conclusions to our environment, where these procedures are almost universally undertaken on an outpatient basis.…”
Section: Scrotal Orchidopexymentioning
confidence: 99%